Estado de conservación de la cobertura de bosques y conectividad del Paisaje en la zona de reserva hidrológica compuesta por las microcuencas de los caños Aguas claras y Caño Cristalino, en el municipio de Cubarral, Meta (2022)
For the area of ​​the Caño Cristalino and Caño Aguas Claras basins, located in the municipality of Cubarral in the department of Meta, a multitemporal and metric analysis was carried out of the landscape, based on a visual analysis of landsat 8 satellite images, with which built the coverage maps corresponding to the years 2014 and 2021. From this analysis it is possible to determine the degree of connectivity of the plant cover of interest, showing the main wildlife transit corridors present in the study area. Through this analysis it is possible to deduce the distribution, concentration and degree of fragmentation that present the different types of coverage present in the area; showing the evolution of state of vegetation cover and landscape connectivity, thus being captured on maps to the year 2014 and 2021. The results of this study give an approximation in knowing the state of conservation of the forest, for being an area of ​​environmental interest, since it is located It borders the Sumapaz National Natural Park and is also a water recharge zone. that supplies the municipal aqueduct of Cubarral, so it must be a protection area for ecosystems, water sources and wildlife.